ANTIMICROBIAL METABOLITES FROM A MARINE-DERIVED FUNGUS - Wilmar Maarisit; Katsuhiro Ueda (Indonesian Journal of Pharmacy, 2013)
A marine fungus was separated from the surface of a marine red algae. Ethyl acetate extract of the cultivated marine fungus inhibited the growth of the pathogenic bacteria E.coli and S.aureus, and the phytopathogenic fungus C. cucurbitarum. Separation of the EtOAc extract gave four compounds, which were identified as new anthraquinonederivatives 3 and 4, and the known chrysophanol (1) and rubelin A (2) by the extensive analysis of NMR data. Compounds 1-4 inhibited the growth of the gram negative bacteria E. coli and gram positive bacteria S. aureus. Compound 3 also inhibited the fungus C. cucurbitarum.Key words: marine-derived fungus, structure elucidation, anthraquinone, antimicrobial activity